Report on the practice in industry in fish preservation. - Ferrer, Severo R. (College of Fisheries, University of the Philippines, 1952)
In order to apply and make use of the knowledge we obtained in the Philippine Institute of Fisheries Technology, we have undergone an extensive apprenticeship in different government and private fishery enterprises. Other objectives of this practice-in-industry is to develop skill among the graduating students and to sought knowledge concerning the ways and methods of preserving fish and other fishery products in different parts of the island. It includes also experimental and research works concerning the nutritional value of fishery products. Fish preservation is a new line of endeavor which is being offered by the Philippine Institute of Fisheries Technology. It takes an individual to give a thorough knowledge of canning, salting, drying and preserving fish and other fishery products for two years of theoretical and laboratory studies and half an year of apprenticeship. So contain in this report are procedures and methods I used during my practice work in which I develop little skill. It includes also the common ways of preserving fish and fishery products of the people of the localities where I took my apprenticeship.